Impaired synthesis and antioxidant defense of glutathione in the cerebellum of autistic subjects: Alterations in the activities and protein expression of glutathione-related enzymes - Gu, Feng; Chauhan, Ved; Chauhan, Abha (Free radical biology & medicine, 2013)
Autism is a neurodevelopmental disorder associated with social deficits and behavioral abnormalities. Recent evidence in autism suggests a deficit in glutathione (GSH), a major endogenous antioxidant. It is not known whether the synthesis, consumption, and/or regeneration of GSH is affected in autism. In the cerebellum tissues from autism (n=10) and age-matched control subjects (n=10), the activities of GSH-related enzymes glutathione peroxidase (GPx), glutathione-S-transferase (GST), glutathione reductase (GR), and glutamate cysteine ligase (GCL) involved in antioxidant defense, detoxification, GSH regeneration, and synthesis, respectively, were analyzed. GCL is a rate-limiting enzyme for GSH synthesis, and the relationship between its activity and the protein expression of its catalytic subunit GCLC and its modulatory subunit GCLM was also compared between the autistic and the control groups. Results showed that the activities of GPx and GST were significantly decreased in autism compared to that of the control group (P<0.05). Although there was no significant difference in GR activity between autism and control groups, 40% of autistic subjects showed lower GR activity than 95% confidence interval (CI) of the control group. GCL activity was also significantly reduced by 38.7% in the autistic group compared to the control group (P=0.023), and 8 of 10 autistic subjects had values below 95% CI of the control group. The ratio of protein levels of GCLC to GCLM in the autism group was significantly higher than that of the control group (P=0.022), and GCLM protein levels were reduced by 37.3% in the autistic group compared to the control group. A positive strong correlation was observed between GCL activity and protein levels of GCLM (r=0.887) and GCLC (r=0.799) subunits in control subjects but not in autistic subjects, suggesting that regulation of GCL activity is affected in autism. These results suggest that enzymes involved in GSH homeostasis have impaired activities in the cerebellum in autism, and lower GCL activity in autism may be related to decreased protein expression of GCLM.